HETEROSIS AND GENETIC PARAMETERS FOR YIELD AND YIELD COMPONENTS IN MAIZE USING HALF DIALLEL CROSS - Rezgar I. S.; M. A. Hussain (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
The study was aimed to determine heterosis, GCA, SCA and some genetic parameters in maize (Zea mays L.). Seeds for half diallel crosses among eight inbred lines Planted in spring season 2021 during fall season 2021, the eight parents and 28 hybrids were sowing (10/7/2021) using Randomize Complete Block Design with three replications at the field of College of Agricultural Engineering Sciences, University of Duhok. The results revealed that the mean square for all genotypes was highly significant effects in all studied traits except number of ears per plant. The (Un44052) line was superior in number of rows per ear and grain yield per plant, while the cross (Zp-505 x Un44052) was superior in number ear per plant and number of rows per ear. Six crosses exhibited significant positive heterosis, the crosses Dkc-f-59 x Dk-17, Dkc-f-59 x Un44052, Dkc-f-59 x Zp-430, Zp-505 x Un44052, Zp-607 x Zp-505 and Zp-179 x Un44052. The heritability in broad sense was higher than the heritability narrow sense in studied traits, between 0.33 and 0.97 for number of ear per plant and grain yield per plant. The average degree of dominance was higher than one in studied traits.